Mangalehen Tuor in the Perspective of Hadith - Sahril, Ahmad (Jurnal Hukum Keluarga, 2024)
Tuor is a term that comes from the Mandailing language which is also called honesty, namely marriage dowry among the Mandailing and Angkola people, where a man is obliged to give tuor to the prospective woman he will marry. However, for some people, young men who are about to marry can be an obstacle to marriage because they are unable to fulfill the requests of the woman's family due to the man's low economic condition. In the Mandailing tradition, the high and low levels of tuor are seen in terms of a woman's status, namely her education, heredity and so on. The aim of this research is to find out the implementation of tuor giving and to find out the community's views on the tradition of giving tuor and also to find out the value of the hadith contained in the tuor tradition in Mandailing customs. This type of field research is descriptive qualitative in nature, while data collection techniques are carried out by means of observation, interviews and documentation. This research can be concluded: first, in terms of history, tuor has existed since the time of the Mandailing kings. Second, the implementation of tuor begins before the wedding day. Third, the basis for the Mandailing community in giving tuor, they rely on the hadiths about dowry. The negative impact of the tuor tradition in Mandailing customs is that it can cancel the marriage, the marriage is delayed, Walimatul 'ursy is only carried out by one party, elopement can be burdensome for a man to get married. Meanwhile, the positive aspect is to avoid divorce, the responsibility of parents towards their children, and so on.